Pengaruh Corporate Governance terhadap Pengungkapan Corporate Social Responsibility - Shiva Aulia Kamal; Mohamad Irsyad (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research aims to determine the influence of corporate governance on corporate social reseponsibility (CSR) disclosure. Governance is measured based on institusional ownership, independent board of commissioners, female board of directors, board of directors, and audit committee. This research uses data sources in the form of secondary data related to financial and sustainability statements with quantitative methods. The sample selection technique used is purposive sampling. A total of 20 companies registered in the Jakarta Islamic Index were used as a sample with 4 years of research, so that the number of observations was 63 observations. Research data processing using Eviews 10 software. The technique of analysis of this research method is panel data regression with the best regression. The results of the study show that female directors have a negative affect on corporate social responsibility (CSR) disclosure. The ownership of the institution, independent commissioners, the size of the board of directors, and the size of the audit committee have no effect on the Corporate Social Responsibility (CSR) disclosure. Meanwhile, leverage as a control variable has a positive influence on corporate social responsibility (CSR) disclosure.